Kaip lietuviai suvokia anglų kalbos junginius - Strimaitienė, Marija; Tankevičiūtė, Marytė (Kalbotyra, 1997)
An auditory experiment was carried out to see whether Lithuanians perceive English consonant dusters not characteristic of Lithuanian. Three groups of auditors took part in the experiment - linguists (students who study French), non-linguists (students who are taught French), and workers. The experiment showed that Lithuanians did not perceive English consonant clusters unusual with Lithuanian. The groups of linguists and non-linguists, however, distinguished them better than the workers. This points to a certain role played by the knowledge of other languages.